Habituation of Arctic ground squirrels (Urocitellus parryii) to handling and movement during torpor to prevent artificial arousal - Christian, Sherri L.; Rasley, Brian T.; Roe, Tanna; Moore, Jeanette T.; Harris, Michael B.; Drew, Kelly L. (Frontiers in Physiology, 2014)
Hibernation is a unique physiological adaptation characterized by periods of torpor that consist of repeated, reversible and dramatic reductions of body temperature, metabolism and blood flow. External and internal triggers can induce arousal from torpor in the hibernator. Studies of hibernating animals often require that animals be handled or moved prior to sampling or euthanasia but this movement can induce changes in the hibernation status of the animal. In fact, it has been demonstrated that movement of animals while they are hibernating is sufficient to induce an artificial arousal, which can detrimentally alter experimental findings obtained from animals assumed to be torpid. Therefore, we assessed a method to induce habituation of torpid hibernators to handling and movement to reduce inadvertent arousals. A platform rocker was used to mimic motion experienced during transfer of an animal and changes in respiratory rate (RR) were used to assess responsiveness of torpid Arctic ground squirrels (AGS, Urocitellus paryii). We found that movement alone did not induce a change in RR, however, exposure to handling induced an increase in respiratory rate (RR) in almost all AGS. This change in RR was markedly reduced with increased exposures, and all AGS exhibited a change in RR≤1 by the end of the study. AGS habituated faster mid-season compared to early in the season, which mirrors other assessments of seasonal variation of torpor depth. However, AGS regained responsiveness when they were not exposed to daily handling. While AGS continued to undergo natural arousals during the study, occurrence of a full arousal was neither necessary for becoming habituated nor detrimental to the time required for habituation. These data suggest that even when torpid, AGS are able to undergo mechanosensory habituation, one of the simplest forms of learning, and provides a reliable way to reduce the sensitivity of torpid animals to handling.